Immune pre-stimulation by injected yeast beta-glucan as a strategy to prevent calf diarrhea and bovine respiratory disease during the first 74 days of age - Yan, Fang; Zhang, Zhihong; Zhan, Xiaorong; Yang, Wenqian; Yao, Junhu; Xu, Xiurong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe complexity of intestinal pathogens poses a great challenge to the prevention of infectious diarrhea in calves. Studies have shown that immune stimulants such as yeast beta-glucan can induce the innate immune system to acquire memory and improve their non-specific defense functions. This trial was conducted to evaluate the prophylactic effect of intraperitoneal injection of yeast β-glucan after birth on diarrhea in Holstein calves during the first 74 days of age.MethodsA total of 52 healthy newborn Holstein calves (body weight 39.3 ± 0.82 kg) were enrolled and randomly assigned into two groups (n = 26 in per group): 1) placebo group (CON), and 2) intraperitoneal injection with yeast β-glucan solution (0.1 g/mL, 50 mg/kg body weight) at 3 and 6 days of age (IP). The CON group received an equal volume of sterile saline at the same time. Body weight was measured monthly, and health checks and fecal consistency were evaluated daily for every calf. Jugular blood and rectal feces were collected at 7 and 30 days of age.ResultsIP induced inflammation in calves, which was manifested as obvious increased levels of serum cytokines (IL-1β, IL-6, and TNF-a), immunoglobulin (IgG and IgM), and oxidative stress after 24 h, and the antimicrobial substance (defensin and secreted immunoglobulin A) in feces also significantly increased, but stimulation didn’t lead to a higher level of serum diamine oxidase (DAO). The pre-stimulation had no positive effect on growth performance or feed efficiency, but reduced the frequencies of diarrhea and bovine respiratory disease, especially during 31-60 d. Furthermore, the pre-stimulation increased the levels of serum IL-6, fecal defensin and secreted immunoglobulin A, while decreased the levels of serum DAO and malonaldehyde at 30 d. In addition, compared with the ones in the CON group, calves in the IP group showed a better rectal bacterial structure at 30 d, with a more enrichment of beneficial bacteria such as Bifidobacterium.DiscussionOur findings suggested that early stimulation with yeast β-glucan could be a promising strategy for reducing the frequencies of both diarrhea and BRD in calves.